Operacije raka danke na Oddelku za abdominalno kirurgijo Splošne bolnice Maribor v petletnem obdobju, 1996-2000 - Krebs, Bojan (Medicinski razgledi, 2004)
Background. Rectal cancer is a highly treatable and often curable disease when localised. The prognosis is clearly related to the degree of tumour penetration through the bowel wall and presence or absence of nodal involvement. The incidence of colorectal cancer in Slovenia is among the highest in malignant diseases. It is the third most common cause of death due to malignant disease in Slovenia. The five-year survival rate is on an increase and was 33 % between 1993 and 1997. Data from all patients operated for rectal cancer were collected from 1996. We used special forms for the preoperative, operative and postoperative part of treatment and a protocol for pathology reports. Most of our patients were followed-up after surgical treatment and their last visit to the hospital was on 1 September 2003. Data on deaths were also obtained from the Central Registry for Cancer in Ljubljana, Slovenia. Statistical analyses were performed using commercially available software - Statistica for Windows. Between the years 1996 and 2003, 285 patients were operated for rectal cancer. The most common operations were abdominoperineal wxcision, low anterior resection and resection of carcinoma with colostomy. 7 % of the procedures involved emergency surgery because of malignant obstruction or bowel perforation. The total 5-year survival was 35 %. The results of surgical treatment of rectal cancer between the years 1996 and 2000 are comparable to those of other studies performed in Slovenia, but inferior to those from Western European countries. We believe that the reasons for this are complex. Nowadays, better results are expected because of the use of new operative techniques (total mesorectal excision), new preoperative oncological therapy and highly trained surgeons specialising in colorectal surgery.
Keywords: Rectal neoplasms; Rektalne novotvorbe; Stadij novotvorbe; Neoplasm staging; Analiza preživetja; Survival analysis; Surgical procedures, operative; Kirurški postopki, operativni; rak (medicina); rektalne bolezni; danka; operativno zdravljenje; preživetje